2021
DOI: 10.3390/nu13092947
|View full text |Cite
|
Sign up to set email alerts
|

It Is High Time for Personalized Dietary Counseling in Celiac Disease: A Systematic Review and Meta-Analysis on Body Composition

Abstract: The body composition of patients with celiac disease (CD), on which the effects of a gluten-free diet (GFD) are controversial, differs from that of the average population. In this study, we aimed to compare the body composition across CD patients before a GFD, CD patients after a one-year GFD and non-celiac control subjects. A systematic search was conducted using five electronic databases up to 15 July 2021 for studies that reported at least one of the pre-specified outcomes. In meta-analyses, weighted mean d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 49 publications
0
10
0
1
Order By: Relevance
“…Weight gain due to the GFD is desirable for some patients but not always beneficial for others. Several studies draw attention to GFD-induced weight gain, which was associated with disproportionate body composition, as it resulted in a substantial gain in FM and a modest increase in FFM [ 13 , 16 , 40 ]. In an Irish study, during a 2-year follow-up, weight gain occurred in 81%, whereas those who were initially overweight continued to gain weight and the proportion of overweight individuals increased from 26% to 51% [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Weight gain due to the GFD is desirable for some patients but not always beneficial for others. Several studies draw attention to GFD-induced weight gain, which was associated with disproportionate body composition, as it resulted in a substantial gain in FM and a modest increase in FFM [ 13 , 16 , 40 ]. In an Irish study, during a 2-year follow-up, weight gain occurred in 81%, whereas those who were initially overweight continued to gain weight and the proportion of overweight individuals increased from 26% to 51% [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Weight gain is desirable in the underweight yet not in those with normal or high body weights. Another problem surfaces when weight gain is mainly due to an increase in body FM rather than in FFM [ 16 ]. Thus, the result of a GFD can be unfavorable regarding body composition and nutrition-related disorders, such as non-alcoholic fatty liver disease (NAFLD) and cardiovascular (CV) events [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Capristo et al, similarly to us, evaluated the nutritional status in two groups: CeD patients at the moment of diagnosis and CeD patients on a GFD, comparing them to healthy controls [ 37 ]; both groups of patients had a lower BMI, FM, and FFM compared to controls, while our data showed only a reduced FFMI at diagnosis. Most nutritional status studies have focused on the pediatric population, as emphasized in a recent meta-analysis and systematic review performed by Vereczkei et al [ 38 ], where five studies of the seven included were conducted on children. This meta-analysis underlined that the few studies conducted on adults, at diagnosis, and during follow-up, had used different techniques to evaluate body composition [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the general perception was that all patients with CD were underweight at the time of diagnosis, while later, either overweight or even obese newly diagnosed CD subjects were also reported. 22 Accordingly, in a study from Minnesota, 27% of the patients with CD were overweight at diagnosis. 23 Moreover, Dickey and Kearney reported that a large minority of Irish patients with CD were overweight before starting GFD.…”
Section: Discussionmentioning
confidence: 99%